The Role of Homecare Nursing in Strengthening Community-Based Disaster Preparedness and Response: A Systematic Review - Hely Hely; Qulliyev Javohirbek G'anijon o'g'li (International Forum of Researchers and Lecturers, 2025)
Disaster preparedness and response are critical components of community health resilience, yet the role of homecare nursing within this framework remains underexplored. This study aims to investigate and synthesize existing research on how homecare nurses contribute to disaster management, with a focus on preparedness and response phases. Employing a systematic literature review (SLR) approach based on the PRISMA 2020 methodology, 38 peer-reviewed articles from major databases were analyzed thematically. Key findings reveal that homecare nurses play significant roles in early warning communication, individualized evacuation planning, and continuity of care post-disaster, particularly for vulnerable populations such as the elderly and chronically ill. However, evidence also indicates substantial gaps in training, policy inclusion, and structural integration into national disaster response systems. Thematic synthesis identified three dominant themes: decentralized preparedness, home-based continuity care, and systemic underrecognition of homecare in emergency frameworks. The study concludes that homecare nursing is a strategic yet underutilized asset in disaster risk reduction and recovery efforts. Strengthening policy, competency frameworks, and formal inclusion of homecare in disaster governance are necessary to enhance community resilience globally.